1999
DOI: 10.2337/diabetes.48.5.1082
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic insulin resistance and defects in substrate utilization in cystic fibrosis.

Abstract: Patients with cystic fibrosis (CF)-related diabetes (CFRD) have clinical features of both type 1 and type 2 diabetes. Past studies have documented peripheral insulin resistance in CF, and some studies have noted high hepatic glucose production (HGP) in CF patients. We hypothesized that patients with CF, similar to patients with type 2 diabetes, have hepatic insulin resistance. Cystic fibrosis is a catabolic condition, yet the etiology of catabolism is poorly understood. De novo lipogenesis is energy wasteful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
2
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 19 publications
3
64
2
4
Order By: Relevance
“…Peak insulin secretion in normal individuals occurs at 30 to 60 minutes, while in CFRD patients it is observed between 90 and 120 minutes. This delay in insulin secretion in the oGTT is related to the loss of the first phase of insulin secretion, which was found in CF patients, even in those who still presented normal glucose tolerance (44).…”
Section: Incidence and Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Peak insulin secretion in normal individuals occurs at 30 to 60 minutes, while in CFRD patients it is observed between 90 and 120 minutes. This delay in insulin secretion in the oGTT is related to the loss of the first phase of insulin secretion, which was found in CF patients, even in those who still presented normal glucose tolerance (44).…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…A clamp study found hepatic insulin resistance with elevated glucose production (in fasting, as well as in response to insulin infusion), occurring equally in diabetic patients and in those who had totally normal fasting glucose levels (44). It has been hypothesized that increased energy needs of CF patients create a physiological balance between elevated hepatic glucose production and high glucose demand (43,44).…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…Alterações na sensibilidade periférica e hepática à insulina vem sendo implicadas 8,[11][12][13][14][15] . Neste estudo encontramos uma correlação significativa entre a insulinemia, representada pela ASC de insulina, e o tempo de doença clinicamente manifesta (Figura 2), o que aponta para uma resistência insulínica progressiva nessa condição.…”
Section: Discussionunclassified
“…Vários estudos demonstraram claramente um comprometimento na secreção de insulina em pacientes mucoviscidóticos [5][6][7][8] , que decorreria da destruição das ilhotas pancreáticas por fibrose, infiltração gordurosa ou deposição de amilóide 2,9,10 . Alterações na sensibilidade à insulina também têm sido implicadas 8,[11][12][13][14][15] . A resistência insulínica nesse distúrbio tem sido justificada por vários mecanismos: infecções pulmonares recorrentes ou crônicas, fibrose hepática subclínica, elevação de hormônios contra-reguladores (cortisol e catecolaminas), níveis elevados de citocinas (interleucinas e TNFa) e, em pacientes com diabetes manifesto, a glicotoxicidade.…”
Section: Study Of the Frequency Of Diabetes Mellitus And Glucose Intounclassified
See 1 more Smart Citation